Individual control over the physical work environment to affect creativity - Samani, Sanaz Ahmadpoor (Korean Institute of Industrial Engineers, 2015)
The purpose of this paper is to provide a review of the background information regarding to the impact of personal control over the physical work environment on satisfaction with work environment and creativity at work. Today creativity has a significant and special place in business especially in innovative organizations which need creative people to generate new, and useful ideas for produce new products, services, work methods, systems etc. Moreover the design and appearance of workspace and individual ability to control the ambient conditions of the workplace have significant effect on their behavior, satisfaction and overall outcome including creativity. So the result of this study will contribute towards enhancing the understanding of the effect of office design to enhance employees' creativity